Analisis Kualitas Fisikokimia Madu Lebah Kelulut (Heterotrigona itama) pada Tiga Lokasi Meliponikultur di Kelurahan Sungai Tiung, Kota Banjarbaru - Siti Afifah; Anang Kadarsah; Sasi Gendro Sari (Universitas Lambung Mangkurat, 2025)
Heterotrigona itama is a stingless bee species that produces high-quality and economically valuable honey. Honey quality assessment can be done through physicochemical parameters according to applicable standards. This study aims to analyze the physicochemical quality of Heterotrigona itama honey from three meliponiculture locations in Sungai Tiung Village, Banjarbaru City and compare it with SNI 8664-2018 and U.S. Patent Application Publication-2011. The study used purposive sampling method by taking samples from Cempaka Madu Kelulut, Cempaka Beton, and Kelulut Kalimantan. Parameters tested included moisture content, total sugar, HMF, reducing sugar, sucrose, acidity, water insoluble solids, ash content, and Pb and Cd metal contamination based on the method in SNI. Data analysis was done descriptively quantitatively. The results showed that all samples had a moisture content of 30-30.33%, total sugar 67.7-68°Brix, HMF 15.3-15.8 mg/kg, reducing sugar 33.88-45.59%, sucrose 7.88-10.58%, acidity 85.33-100 mL NaOH/kg, water insoluble solids 0.35-1.15%, ash content 0.056-0.1%, and Pb and Cd contamination <0.0001 mg/kg. Most parameters met the SNI, while the water content, reducing sugar, and sucrose exceeded the set limits.